MOTIVASI DAN LINGKUNGAN KERJA: FAKTOR KUNCI DALAM MENINGKATKAN KINERJA KARYAWAN DI STATION CCTV - Melinda, Widia; Puspasari, Mardiana; Muslimin, Amrah; Fitantina, Fitantina (Universitas Muhammadiyah Palembang, 2024)
Purpose– This research aims to determine the influence of motivation and work environment on the performance of employees of Station CCTV Palembang Branch.Design/methodology–The type of research used is associative research. The independent variables in this research are motivation and work environment, while the dependent variable is employee performance. The population in this study included all permanent employees at the Station CCTV Palembang Branch, totaling 50 people, with a sample of 33 respondents using the Slovin 10% formula, with a sampling technique using proportionate stratified random sampling. Primary data in this research was obtained from questionnaires, while secondary data was obtained from documentation. The data analysis techniques used are multiple linear regression analysis, hypothesis testing (F test and t test), and coefficient of determination.Findings - The results of the F test (simultaneous) prove that there is a significant influence of motivation and work environment on the performance of employees of Station CCTV Palembang Branch. The results of the t test (partial) prove that there is a significant influence of motivation on employee performance, and there is a significant influence of the work environment on the performance of employees of Station CCTV Palembang Branch. The results of the coefficient of determination show that motivation and work environment are able to contribute to increasing the performance of employees at Station CCTV Palembang Branch, amounting to 78.1%.